Sex Differences in CGRP Regulation and Function in the Amygdala in a Rat Model of Neuropathic Pain - Presto, Peyton; Neugebauer, Volker (Frontiers in Molecular Neuroscience, 2022)
The amygdala has emerged as a key player in the emotional response to pain and pain modulation. The lateral and capsular regions of the central nucleus of the amygdala (CeA) represent the “nociceptive amygdala” due to their high content of neurons that process pain-related information. These CeA divisions are the targets of the spino-parabrachio-amygdaloid pain pathway, which is the predominant source of calcitonin gene-related peptide (CGRP) within the amygdala. Changes in lateral and capsular CeA neurons have previously been observed in pain models, and synaptic plasticity in these areas has been linked to pain-related behavior. CGRP has been demonstrated to play an important role in peripheral and spinal mechanisms, and in pain-related amygdala plasticity in male rats in an acute arthritis pain model. However, the role of CGRP in chronic neuropathic pain-related amygdala function and behaviors remains to be determined for both male and female rats. Here we tested the hypothesis that the CGRP1 receptor is involved in neuropathic pain-related amygdala activity, and that blockade of this receptor can inhibit neuropathic pain behaviors in both sexes. CGRP mRNA expression levels in the CeA of male rats were upregulated at the acute stage of the spinal nerve ligation (SNL) model of neuropathic pain, whereas female rats had significantly higher CGRP and CGRP receptor component expression at the chronic stage. A CGRP1 receptor antagonist (CGRP 8-37) administered into the CeA in chronic neuropathic rats reduced mechanical hypersensitivity (von Frey and paw compression tests) in both sexes but showed female-predominant effects on emotional-affective responses (ultrasonic vocalizations) and anxiety-like behaviors (open field test). CGRP 8-37 inhibited the activity of CeA output neurons assessed with calcium imaging in brain slices from chronic neuropathic pain rats. Together, these findings may suggest that CGRP1 receptors in the CeA are involved in neuropathic pain-related amygdala activity and contribute to sensory aspects in both sexes but to emotional-affective pain responses predominantly in females. The sexually dimorphic function of CGRP in the amygdala would make CGRP1 receptors a potential therapeutic target for neuropathic pain relief, particularly in females in chronic pain conditions.